Water quality analysis and the occurrence of antibiotic - resistant bacteria (ARB) from Satow Waterfall in Bau, Malaysian Borneo - Khairunnisa Mohammad Hamdi,; Samuel Lihan,; Stanley Sait,; Scholastica Ramih,; Nur Azzah Osman,; Nur Nazifah Mohamad,; Tay, Meng Guan,; Fazia Mohamad Sinang,; Hashimatul Fatma Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Water quality monitoring of a particular river is crucially important to determine if the river water meets the requirement for its designated uses. Therefore, an assessment of the physiochemical water quality at Satow Waterfall, Sarawak, and the prevalence of antibiotic-resistant bacteria (ARB) was conducted to corroborate the safety of the water from the waterfall. A total of 42 water samples were collected at the subsurface water of the upstream, midstream, and downstream on two sampling trips in June 2021 (dry season) and December 2021 (wet season), with six months intervals. The water quality index (WQI) of the sampling stations ranged from 92.60 to 95, classifying the water under Class I. However, the water is microbiologically polluted, with the highest coliform count of 2.59 × 105 CFU/ mL recorded at the middle stream during the wet season, which has surpassed the regulatory standard set by the Malaysian Department of Environment (DOE). A total of 54 bacterial isolates were chosen as representatives and identified by 16S rRNA sequencing, which confirmed the existence of 21 bacterial genera. All identified isolates were tested against 15 antibiotics of various classes employing the Clinical and Laboratory Standards Institute (CLSI) protocols. The antibiotic susceptibility test (AST) demonstrated substantial resistance to sulfamethoxazole (48%) and erythromycin (48%), as well as high susceptibility to chloramphenicol (84%), levofloxacin (60%) and ofloxacin (60%). The Multiple Antibiotic Resistance Index (MARI) evaluations demonstrated the MARI varied from 0-0.60, with 33% of the isolates having a MARI greater than 0.2. In this study, the occurrence of ARB in a water environment where there is an undisclosed source of antibiotic utilization is still inevitable, highlighting the necessity to constantly monitor the water quality and the pervasiveness of ARB in recreational water.